Reading as Cultural Capital and Social Interaction - Lapienienė, Audronė; Mažeikienė, Natalija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article focuses on the social aspects of reading.Conceptual framework of cultural capital is usedin order to actualise the importance of sociocultural and socioeconomic factors in family and at school for the child’s reading. The research reveals complex and multifaceted development of children’s reading skills: different factors such as cultural environment, cultural activity, and cultural objects in family and at school (in the classroom and library) interact and increase the possibilities for the child to acquire and integrate social knowledge.Aim of the researchis to analyse the interplay between educational and social factors during formation of reading in pupils. The following objectives have been set out to reach this aim: 1) to perform literature review of reading as social interaction and cultural capital, social factors determining reading in children; 2) to reveal the interplay between educational and social factors during formation of the children’s reading habitus by conducting interviews with the expert focus group.Methods of the research:group interviews with 24 experts of reading – primary school teachers, authors of textbooks of Lithuanian language and reading comprehension for primary schools, publishers of textbooks for primary schools were conducted.